Clinical Trial of Tuberculosis Vaccine in Indonesia: Balancing Public Health Needs and Legal Protection for Research Subjects - Tony Richard Alexander Samosir; Anita Afriana; Efa Laela Fakhriah (International Journal Labs, 2025)
Clinical trials are an important instrument in the development of science and technology in the health field that aims to produce safe and effective medical interventions. The implementation of research involving human subjects cannot be carried out without clear guidelines, ethical standards, and legal frameworks. In the Indonesian context, various stages and procedures have been established to ensure that clinical trials, including the Tuberculosis (TB) vaccine clinical trials that have been carried out, run in accordance with legal principles and medical ethics. This study uses a normative juridical method by relying on secondary data through library research. The focus of the analysis is directed at laws and regulations, public policies, and official documents that regulate the management of vaccine clinical trials in Indonesia. The results of the study show that: First, the implementation of TB vaccine clinical trials in Indonesia must be based on the provisions of national health law by upholding the principles of utility, morality, religious values, moral norms and oriental norms, as well as compliance with all relevant laws and regulations. Second, public health interests can be the basis for restricting individual rights in the implementation of clinical trials, as long as there is strong scientific evidence regarding the potential for the rapid and dangerous spread of infectious diseases, so that the action is proportionate and has legal legitimacy.